نمذجة التواصل من خلال القرآن الكريم - بوشريط نور الهدى; ديدة يمينة (University of Eloued جامعة الوادي, 2024)
"جاءت هذه الدراسة بعنوان نمذجة التواصل من خلال القرآن الكريم والتي تهدف إلى بيان أهمية التواصل في حياة الفرد وكذلك إبراز أهم أنواع التواصل من خلال القرآن الكريم إلى جانب معرفة كيف اعتنى القرآن الكريم بهذا التواصل مبرزا المهارات المؤدية لنجاحه محذرا من الأمور التي تقطعه، حيث تمحورت إشكالية هذه الدراسة في: فيما تتمثل نمذجة التواصل من خلال القرآن الكريم؟ ماهي أهم أنواع التواصل فيه؟ ومن خلال البحث في هذه الدراسة توصلنا إلى النتائج الآتية ✓تكمن أهمية الاتصال في كونه أساس تركيبة المجتمعات الإنسانية. ✓من أهم أنواع وأشكال التواصل التي تطرق إليها القرآن واعتنى بها نجد: التواصل مع الاسرة-التواصل في المجتمع-التواصل الدعوي. ✓تعتبر الأسرة اللبنة الأولى للمجتمع فالقرآن الكريم حث على أهمية المودة والرحمة في التواصل بين أفراد الأسرة الواحدة. ✓عظم القرآن الكريم شأن الوالدين بحيث أعطى آيات واضحة بينت كيفية تعامل الأبناء مع آبائهم بطريقة صحيحة. ✓يتفرد الإنسان عن سائر الكائنات بقدرته على التواصل، تلك المهارة التي تمكنه من تبادل الأفكار والمشاعر، وبناء العلاقات والتعبير عن ذاته واكتشاف العالم من حوله، فالتواصل ركيزة أساسية للحضارة الإنسانية لهذا فالإنسان بطبعه كائن اجتماعي، لا يمكنه العيش بمعزل عن الآخرين فهو دائما محتاج للتواصل معهم في مختلف جوانب حياته، ولا يقتصر هذا التواصل على استخدام اللغة الشفاهية فقط بل يتعداها ليشمل استخدام الإشارات الجسدية كلغة الجسد وغيرها. ✓يعتبر التواصل الدعوي من أهم واجبات المسلمين، ولابد لكل مسلم أن يسعى للمساهمة في نشر الدعوة الإسلامية وتعليمها للناس كافة وذلك من خلال إتباع الاساليب التي انتهجها القرآن الكريم والمتمثلة في: الحكمة-الموعظة الحسنة-المجادلة-القدوة الحسنة. "This study was titled Modeling Communication Through the Holy Qur’an, which aims to explain the importance of communication in an individual’s life, as well as highlighting the most important types of communication through the Holy Qur’an, in addition to knowing how the Holy Qur’an took care of this communication, highlighting the skills that lead to its success and warning of the things that interrupt it. The problem of this study revolved around: What is the modeling of communication through the Holy Qur’an? What are the most important types of communication in it? Through research in this study, we reached the following results: ✓The importance of communication lies in the fact that it is the basis of the structure of human societies. ✓ Among the most important types and forms of communication that the Qur’an touched upon and paid attention to, we find: communication with the family - communication in society - communication for advocacy. ✓The family is considered the first building block of society. The Holy Qur’an urges the importance of affection and compassion in communication between members of the same family. ✓ The Holy Qur’an magnified the importance of parents, giving clear verses that showed how children should deal with their parents in a correct manner. ✓Man is unique from other creatures in his ability to communicate, a skill that enables him to exchange ideas and feelings, build relationships, express himself, and discover the world around him. Communication is an essential pillar of human civilization. Therefore, man is by nature a social being. He cannot live in isolation from others, as he always needs communication. With them in various aspects of his life, this communication is not limited to the use of oral language only, but goes beyond it to include the use of physical signals such as body language and others. ✓Dawah communication is considered one of the most important duties of Muslims, and every Muslim must strive to contribute to spreading the Islamic call and teaching it to all people by following the methods followed by the Holy Qur’an, which are: wisdom - good advice - debate - good example "
Keywords: نمذجة التواصل ، القرآن الكريم، الأسرة، حياة الفرد، المجتمع; Communication modeling; Holy Quran; family; individual life; society